Nexus disrupted: Lived realities and the water-energy-food nexus from an infrastructure perspective. Issue 133 (July 2022) - Bruns, Antje; Meisch, Simon; Ahmed, Abubakari; Meissner, Richard; Romero-Lankao, Patricia
Highlights: Critical intervention to WEF-Nexus studies by looking at lived experienced realities. Understanding WEF-Nexus as heterogeneous infrastructure configuration. Multiple Nexuses can co-exist and they are dynamic over time and space. Nexus-Governance needs to address differentiated inequalities and insecurities. Agency to (re-)configure the Nexus is distributed across different degrees of formality. Abstract: In recent years, the water-energy-food nexus gained traction in science and policy debates to address the relationships between water, energy and food sectors. Inspired by Political Ecology thinking, we advocate for a nexus understanding that acknowledges the political nature of the concept and points to lived and experienced nexus realities. We draw on literature from heterogeneous infrastructures, giving attention to the socio-material entanglements that configure a nexus dynamically over time and space. We substantiate our conceptual arguments based on three different cases from Sub-Saharan Africa, that reveal the ways in which people access, maintain or disrupt infrastructure that links water, energy, and food systems. This may occur through practice forms of tinkering or improvisation of infrastructural components, intermediate (decentralised) technologies, through theft, or through some form of self-empowerment. Methodologically, the role of practices is emphasized as they help to understand Nexus heterogeneity and disparate forms of agency to (re-)configure a nexus. The findings demonstrate that the nexus is not just there but is constantly in-the-making. Practices stabilise, build, or alter differentiated nexus configurations within uneven nexus in/securities. Moreover, this article disrupts a "one-size-fits-all" nexus concept by offering a nuanced understanding of nexus realities that are more complex, heterogeneous, and plural than commonly described. Our analysis shows that re-thinking the nexus by focusing on people and practices draws the attention towards agency and change – and thus enables to identify leverage themes rendering a more just nexus.